Novel lunge biomechanics in modern sabre fencing - Moore, K. C.; Chow, F. M. E.; Chow, J. Y. H. (Procedia Engineering, 2015)
Sabre is one of the three disciplines in the sport of fencing, characterised by the use of a lightweight cutting weapon to score hits on an opponent while maneuvering for position with rapid and dynamic footwork. One of the main techniques is the lunge: an explosive extension of the fencer's body propelled by the non-dominant (ND) leg in which the dominant (D) leg is kicked forward. The lunge provides both power and range (up to 3m) to the fencer and helps accelerate the sword for a rapid strike. Classical fencing lunges differ in style but share a common mechanism: a forward leap originating in the ND leg that powers rotation in a highly mobile thoracic cage. A new generation of fencers has begun to deviate from the classical lunge mechanism in recent years with a ND leg adopting a rigid momentum-conserving structure. This constant ND knee extension yields a constant rotational acceleration of the pelvis toward the dominant side and emphases scapular rotation to transfer power to the sword arm compared to thoracic rotation in classical lunges. We hypothesized that the new lunge mechanism delivers greater power, efficiency, range, and acceleration than the classical lunge. We measured the range, speed and acceleration of ten lunges at maximal exertion following a forward step using video capture from each of twenty-one (21) amateur subjects, aged between 10 to 55 years and in experience from 1 to 15 years. We assessed the performance of each subjects` lunge on five measures of alignment from both frontal and lateral videos, then used linear regression to identify correlations between significant markers of alignment and performance. These videos were also compared to competition videos of four (4) current fencers on the international competition circuit (Fédération Internationale d`Escrime, FIE) to verify our analyses with professional athletes.